1994
DOI: 10.1016/0014-5793(94)80143-6
|View full text |Cite
|
Sign up to set email alerts
|

Specific receptors for adrenomedullin in cultured rat vascular smooth muscle cells

Abstract: The effects of synthetic rat adrenomedullin (rAM), a novel vasorelaxant peptide originally isolated from human pheochromocytoma. on receptor binding and CAMP generation were studied in cultured rat vascular smooth muscle cells (VSMC). A binding study using ["51]rAM revealed the presence of a single class of high-affinity (& 1.3 x lo-* M) binding sites for rAM m VSMC. The apparent K, of rat calcitonin gene-related peptide (rCGRP) was 3 x lo-' M. Affinity labeling of VSMC membranes with ["'I]rAM revealed two dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(122 citation statements)
references
References 11 publications
(12 reference statements)
8
114
0
Order By: Relevance
“…In fact, there is much difference among species in the vasodilating effect, in cAMP production, and in the affinity of adrenomedullin. 29,31 A significant antiapoptotic effect of adrenomedullin was observed at 10 Ϫ7 mol/L. Baseline adrenomedullin levels in the culture medium of HUVECs were substantially low.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, there is much difference among species in the vasodilating effect, in cAMP production, and in the affinity of adrenomedullin. 29,31 A significant antiapoptotic effect of adrenomedullin was observed at 10 Ϫ7 mol/L. Baseline adrenomedullin levels in the culture medium of HUVECs were substantially low.…”
Section: Discussionmentioning
confidence: 93%
“…1 Adrenomedullin is believed to promote the relaxation of vascular smooth muscle cells through a cAMP/ protein kinase A pathway. 29 Adrenomedullin also elevates intracellular cAMP level in other cell types, including endothelial cells. 30 In the present study, cAMP analogs or a cAMP-elevating reagent failed to mimic the antiapoptotic effect of adrenomedullin.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was inconsistent with previous research in which a high concentration of immunoreactive ADM was found ubiquitously in all pulmonary tissue examined, including VSMCs and ECs, 6 and a high expression level of ADM mRNA was found in the lungs as well as in the adrenal glands. [7][8][9] This discrepancy can be explained by the possibility that ADM and ADT are synthesized by ECs and VSMCs as well, and that which is biosynthesized in the ECs is rapidly and continuously secreted into the blood or functions as an autocrine or paracrine regulator. 10 However, the ADM and ADT that is synthesized by VSMCs may be stored in the smooth muscle cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…This caused a transient increase (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in perfusion pressure. The preparations were then rinsed with SD-free Krebs solution for 1 h.…”
Section: Chemical Removal Of Vascular Endotheliummentioning
confidence: 99%